2020
DOI: 10.1109/access.2020.2965931
|View full text |Cite
|
Sign up to set email alerts
|

Use of Doppler and Doppler Rate for RF Geolocation Using a Single LEO Satellite

Abstract: A passive radio frequency (RF) geolocation solution is provided that uses a single low earth orbit (LEO) satellite to find an uncooperative earth-bound emitter. For the first time, an unambiguous solution is available for real-time, single-pass, and time-constrained acquisition scenarios where single transmissions are expected. The geolocation algorithm rapidly maps Doppler and Doppler rate measurements to an RF emitter location. Corresponding theoretic performance bounds are provided for mission analysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Thus, it is easier to apply restrictions to cUKF filters, which are natural when performing the tasks of determining the location of radio emission sources. In [38], the errors in determining the ephemeris and the influence of oscillator drift were considered. However, all the considered works do not take into account the rotation of the Earth, which can affect the accuracy in determining the location of radio emission sources.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it is easier to apply restrictions to cUKF filters, which are natural when performing the tasks of determining the location of radio emission sources. In [38], the errors in determining the ephemeris and the influence of oscillator drift were considered. However, all the considered works do not take into account the rotation of the Earth, which can affect the accuracy in determining the location of radio emission sources.…”
Section: Methodsmentioning
confidence: 99%
“…Assuming a carrier can be extracted from an interference signal, single‐satellite‐based transmitter geolocation is possible from Doppler measurements alone (Becker, 1992; Ellis et al., 2020). The analysis presented here emphasizes the effect of transmitter clock stability on geolocation accuracy.…”
Section: Single‐satellite Terrestrial Source Geolocationmentioning
confidence: 99%
“…The authors in [ 23 ] have shown a new algorithm for estimating the downlink Doppler frequency of LEO satellites as the main measurements of Doppler positioning systems in Nav-SOP applications. Moreover, the analysis of using Doppler and Doppler rate of LEO satellites for Radio Frequency (RF) geolocation and enhancement of Doppler positioning algorithms for stand-off trajectories are studied in [ 24 , 25 ], respectively. A Precise Point Positioning (PPP) system was also designed and validated in [ 26 , 27 ].…”
Section: Related Workmentioning
confidence: 99%